Temperature Dependence of Viscosities of Heptamethylene Dibromide Solutions in Ethanol at 288-323 K - Li, Hua; Chen, Xiaoshuang (Asian Journal of Chemistry, 2015)
The densities and viscosities of heptamethylene dibromide in ethanol had been determined from (288.15 to 323.15) K. The relative viscosities were correlated using the Surtherland-Wassiljewa equation. The results showed that the model agreed well with the experimental data.